2022
DOI: 10.1002/1878-0261.13222
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and cancer: a research gap to fill

Abstract: The complex mechanisms of ageing biology are increasingly understood. Interventions to reduce or delay ageing-associated diseases are emerging. Cancer is one of the diseases promoted by tissue ageing. A clockwise mutational signature is identified in many tumours. Ageing might be a modifiable cancer risk factor. To reduce the incidence of ageing-related cancer and to detect the disease at earlier stages, we need to understand better the links between ageing and tumours. When a cancer is established, geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 140 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…There are almost 4 million new patients and over 1.9 million deaths annually in Europe, with cancer accounting for 25% of deaths in Europe [ 1 ]. Population ageing is the main factor contributing to the increase in cancer incidence and mortality, impacting on society and healthcare [ 2 ]. Importantly, with new, more effective treatment modalities, cancer survivors have increased to nearly 20 million in Europe [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are almost 4 million new patients and over 1.9 million deaths annually in Europe, with cancer accounting for 25% of deaths in Europe [ 1 ]. Population ageing is the main factor contributing to the increase in cancer incidence and mortality, impacting on society and healthcare [ 2 ]. Importantly, with new, more effective treatment modalities, cancer survivors have increased to nearly 20 million in Europe [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout history, cancer has been a major health problem. It has been shown that there is a positive correlation between cancer incidence and age [ 1 , 2 , 3 ]. The individual risk of cancer is also influenced by family history, genetic susceptibility or behaviour, and exposure to carcinogenic factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%